(untitled) (Nigerian Journal of Physiological Sciences, 2023)
Cattle egret (Bubulcus ibis) is a cosmopolitan heron species, with least concern conservation status. There are limited literatures on the anatomy of this bird, especially in relation to its sensory organs, hence we here investigated the gross morphological and histomorphometric features of its tongue. The tongues of twelve healthy juvenile cattle egrets were examined in situ for morphological appearance and gross morphometric measurements were determined ex situ. Routine histology was conducted on the tongue tissue with parameters such as epithelial and lamina propia heights, lingual muscle and entoglossal cartilage heights evaluated. Grossly, the tongue was divided into three parts name; apex, body and the root. It was arrow shaped, conforming to the shape of the beak, with a laryngeal mound bounded caudally by the pharyngeal papillae at its root. A massive entoglossal cartilage formed the core of the cranial apex, ventral body portion, and caudal aspect of the root. Histologically, the lingual mucosa possessed keratinized squamous epithelium in all its divisions, with spinous conical papillae being characteristic of the cranial apical mucosa. The body lingual mucosa possessed foliate papillae on the dorsal aspects, while filiform papillae were prominent in the ventral portions. The lingual root uniquely possessed numerous glandular ducts in its lamina propia as well as localized adipocytes. Overall, the regression analysis data showed that the body weight can be conveniently predicted from tongue parameters. This study has thus provided additional knowledge on the anatomy of the birds and the generated data could prove useful in comparative regional anatomy.